Primary Progressive Aphasia and Apraxia of Speech - Jung, Youngsin; Duffy, Joseph R.; Josephs, Keith A. (Seminars in Neurology, 2013)
Primary progressive aphasia is a neurodegenerative syndrome characterized by progressive language dysfunction. The majority of primary progressive aphasia cases can be classified into three subtypes: nonfluent/agrammatic, semantic, and logopenic variants. Each variant presents with unique clinical features, and is associated with distinctive underlying pathology and neuroimaging findings. Unlike primary progressive aphasia, apraxia of speech is a disorder that involves inaccurate production of sounds secondary to impaired planning or programming of speech movements. Primary progressive apraxia of speech is a neurodegenerative form of apraxia of speech, and it should be distinguished from primary progressive aphasia given its discrete clinicopathological presentation. Recently, there have been substantial advances in our understanding of these speech and language disorders. The clinical, neuroimaging, and histopathological features of primary progressive aphasia and apraxia of speech are reviewed in this article. The distinctions among these disorders for accurate diagnosis are increasingly important from a prognostic and therapeutic standpoint.
Keywords: dementia; primary progressive aphasia; apraxia of speech